Ideology, socialization and hegemony in Disciplinary International Relations. - Persaud, Randolph B (International Affairs, 2022)
This article argues that Disciplinary International Relations (DIR) does not only explain international affairs, but it also socializes and hegemonizes publics and professionals into an ideological worldview consistent with the interest of states that underwrite the world economic and security order based on hegemonic liberalism. Considerable emphasis is placed on tracing the continuities between the early theorization of IR in the United Kingdom and the United States, and the contemporary academic/foreign policy/security 'complex' dedicated to the maintenance of a hegemonic world order. The article demonstrates that the call for a greater theory–policy nexus in international affairs is redundant because leading American scholars double up as policy-makers, either directly or through other avenues such as consultancies. Some of the most prominent IR scholars, such as Michael Doyle, John Lewis Gaddis, Samuel Huntington, G. John Ikenberry, Stephen Krasner, Theodore H. Moran, Joseph Nye and Anne-Marie Slaughter, among others, have served in high-level positions in the United States foreign policy and security apparatus. The article also shows the ways in which in the early days of IR theorizing in the UK, scholars such as Lionel Curtis, Alfred Zimmern and Norman Angell doubled as staunch defenders of the British Empire, albeit in the language of liberal internationalism.